Pengaruh Metode Eksperimen Terhadap Hasil Belajar IPA Materi Perubahan Wujud Benda Siswa Kelas III SD Negeri 17 Kota Pekanbaru - Putri, Dona Asmarani; Fitriyeni, Fitriyeni (LPPM Institut Pendidikan Nusantara Global, 2026)
This study aims to examine the effect of the experimental method on students’ learning outcomes in science, particularly on the topic of changes in the states of matter, among third-grade students at SD Negeri 17 Kota Pekanbaru. The research employed a quantitative approach using an experimental method with a one-group pretest–posttest design. The participants were 30 students from class III D, while the object of the study was the implementation of the experimental method in science learning. Data were collected through observation, interviews, tests, and documentation. The research instruments were validated through validity and reliability tests, item difficulty level analysis, and discrimination index testing. Data analysis was conducted using a normality test and hypothesis testing with a t-test. The results showed a significant improvement in students’ learning outcomes after the implementation of the experimental method. The mean pretest score of 50.66% increased to 75.00% in the post-test, indicating an improvement in students’ understanding of the concept of changes in the states of matter. The results of the paired sample t-test revealed a significance value (Sig. 2-tailed) of 0.000, which is lower than 0.05, indicating a statistically significant difference between pretest and post-test scores. Based on these findings, it can be concluded that the experimental method has a positive and significant effect on science learning outcomes of third-grade students at SD Negeri 17 Kota Pekanbaru. This method is effective because it actively involves students in the learning process through hands-on experimental activities.